Water production from food processing wastewaters using integrated membrane systems: A sustainable approach - Roberto Castro-Muñoz; Vlastimil Fíla; Víctor M. Rodríguez-Romero; Jorge Yáñez-Fernández (Tecnología y ciencias del agua, 2017)
Castro-Muñoz, R., Fíla, V., Rodríguez-Romero, V. M., & Yáñez-Fernández, J. (November-December, 2017). Water production from food processing wastewaters using integrated membrane systems: A sustainable approach. Water Technology and Sciences (in English), 8(6), 129-136,